Online ion‐exchange chromatography for small‐angle X‐ray scattering. Issue 10 (9th November 2016) - Hutin, Stephanie; Brennich, Martha; Maillot, Benoit; Round, Adam
Abstract : SAXS coupled with online ion‐exchange chromatography allows the collection of high‐quality BioSAXS data. Abstract : Biological small‐angle X‐ray scattering (BioSAXS) is a powerful technique to determine the solution structure, particle size, shape and surface‐to‐volume ratio of macromolecules. However, a drawback is that the sample needs to be monodisperse. To ensure this, size‐exclusion chromatography (SEC) has been implemented on many BioSAXS beamlines. Here, the integration of ion‐exchange chromatography (IEC) using both continuous linear and step gradients on a beamline is described. Background subtraction for continuous gradients by shifting a reference measurement and two different approaches for step gradients, which are based on interpolating between two background measurements, are discussed. The results presented here serve as a proof of principle for online IEC and subsequent data treatment.